Leadership Management in Improving the Social Economy of the Community with the Help of Digital Technology - Nurjaya; Rahmat; Muhammad Nasir (Universitas Pendidikan Ganesha, 2025)
The problem of this research is the challenges faced by Micro, Small, and Medium The problem of this research is the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in implementing the concept of economic management in the digital era. The urgency of this research is to understand the role of MSMEs in the Indonesian economy, which absorbs more than 97% of the workforce and contributes approximately 60% to Gross Domestic Product. The aim is to explore the role of economic management in increasing the competitiveness and desirability of MSMEs. The research method used is a mixed approach, including a quantitative survey conducted on MSME business actors and in-depth interviews to gain contextual understanding. A sample of 217 students running MSMEs was randomly selected. Data collection techniques included questionnaires and interviews. Data analysis techniques used descriptive statistical analysis for quantitative data and qualitative analysis for interview data. The results of the study indicate that many students running MSMEs experience difficulties in understanding economic management and implementing digital technology. The conclusions and implications of this research emphasize the need for improved education and training in the field of economic management as well as government support to increase the capacity of assistance to vocational school students in running MSMEs and assisting them in facing market changes in the digital era.